Human Resource Management in the Digital Era: Case Study of Recruitment and Career Development in the Indonesian Banking Sector - Ce Mulya Rizki Anugrah; Fithri Suciati; Wawan Ruswandi; Heri Patandung (Dinasti International Journal of Education Management And Social Science, 2024)
In this digital era, the changes that occur in a company move quickly, so companies must be able to adapt and have a strategy so as not to be disturbed by current developments, one of which is managing and paying attention to the quality of human resources. well, which can start with quality recruitment patterns and appropriate career development, including in the banking sector. The aim of this research is to find out how human resources are managed, especially patterns of worker recruitment and career development carried out by the banking sector in Indonesia. The method used in this research is descriptive analysis, with the main data source being the financial reports of BRI and Bank Mandiri. The research results show that there are similarities in the recruitment and career development patterns of the four banks, namely the use of digital technology in recruitment and career development, digital skills possessed by workers, and competency-based career development. Apart from similarities, there are also several differences, including the recruitment methods used and career development programs, which are influenced by the company's strategic focus.